2012
DOI: 10.1038/pcan.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity in patients receiving adjuvant docetaxel + hormonal treatment after radical radiotherapy for intermediate or high-risk prostate cancer: a preplanned safety report of the SPCG-13 trial

Abstract: and for the SPCG-13 BACKGROUND: Radical radiotherapy (RT) combined with androgen deprivation therapy is currently the standard treatment for elderly patients with localized intermediate-or high-risk prostate cancer (PC). To increase the recurrence-free and overall survival, we conducted an adjuvant, randomized trial using docetaxel (T) in PC patients (Scandinavian Prostate Cancer Group trial 13). METHODS:The inclusion criteria are the following: men 418 and p75 years of age, WHO/ECOG performance status 0--1, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The current analysis is the first study reporting a single germline variant associated with aggressive PCa and with outcome of mCRPC after docetaxel treatment. This is an especially important finding taking into account the possible adjuvant use of docetaxel in high-risk PCa (21)(22)(23). Moreover, ANO7 is not a DNA-repair gene, therefore revealing there must be another pathway underlying the response to docetaxel.…”
Section: Discussionmentioning
confidence: 95%
“…The current analysis is the first study reporting a single germline variant associated with aggressive PCa and with outcome of mCRPC after docetaxel treatment. This is an especially important finding taking into account the possible adjuvant use of docetaxel in high-risk PCa (21)(22)(23). Moreover, ANO7 is not a DNA-repair gene, therefore revealing there must be another pathway underlying the response to docetaxel.…”
Section: Discussionmentioning
confidence: 95%
“…The sponsor stopped the study early, and data are currently being collected and analysed through a multi‐institutional registry (NCT01813370). The Scandinavian Prostate Cancer Group (SPCG) 15 study of adjuvant docetaxel after radiotherapy reported high rates of neutropenia . A similar study, Prostate Cancer Consortium in Europe (PEACE) 2 (NCT01952223), will assess cabazitaxel plus pelvic radiotherapy in patients with high‐risk localised prostate cancer.…”
Section: When To Begin Chemotherapy?mentioning
confidence: 99%
“…Standard chemotherapies, while effectively killing cancer cells, also result in adverse side effects 44,45 . Encapsulation of cytotoxic agents in micro/nanoparticles has emerged over the last two decades as a promising approach to overcome some of the challenges in systemic delivery of such therapeutics 9,46 .…”
Section: Resultsmentioning
confidence: 99%